Dynamics of Toxic Work Environments and Job Satisfaction: Analyzing the Mediating Role of Self-Efficacy and the Moderation of Social Support - Mariano Firmansyah; David Manafe; Septiani Arbania (Poltanesa, 2026)
This study aims to analyze in depth the influence of toxic work environments on employee job satisfaction in Kupang City, examining the role of self-efficacy as a mediating variable and social support as a moderating variable. While unhealthy work environments are often regarded as a primary factor in declining morale, this research explores the underlying psychological mechanisms behind such impacts. Employing a quantitative approach, data were collected via questionnaires from employees in Kupang City and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the structural relationships between variables.The results indicate that social support is a strong predictor that positively influences job satisfaction. Conversely, toxic work environments are confirmed to have a general negative impact on job satisfaction. However, a unique finding reveals that a toxic work environment actually enhances employee self-efficacy. Furthermore, self-efficacy is proven to act as a mediator that bridges the relationship between a toxic work environment and job satisfaction.Nonetheless, moderation testing demonstrates that social support is unable to weaken the negative influence of a toxic work environment on job satisfaction. This finding emphasizes that emotional support among colleagues has limitations in mitigating the effects of a destructive organizational culture. Therefore, systemic interventions to improve management and organizational culture are far more crucial than merely relying on internal social relations.